Kennel Disinfectants for Microsporum canis and Trichophyton sp. - Karen A. Moriello (Veterinary Medicine International)
The antifungal efficacy of commonly used kennel disinfectants for large surfaces was tested using naturally infective material from untreated animals (M. canis and Trichophyton sp.) soaked and macerated but unfiltered leaving visible fluorescing hairs and/or scales in the test inoculum to create a robust challenge. Disinfectants included sodium hypochlorite (1 : 32 and 1 : 100), enilconazole (1 : 100), accelerated hydrogen peroxide (1 : 16), potassium peroxymonosulfate (1% and 2%), and calcium hypochlorite “dry bleach.” Disinfectants were tested at a 1 : 10, 1 : 5, and 1 : 1 dilution of test inoculum to disinfectant with a 10 min contact time. Good efficacy was defined as a disinfectant resulting in no growth. Control plates grew >300 colonies of each pathogen per plate. Enilconazole, sodium hypochlorite (all dilutions), accelerated hydrogen peroxide, and 2% potassium peroxymonosulfate (but not 1%) inhibited all growth of both pathogens at 1 : 10, 1 : 5, and 1 : 1 dilutions. Calcium hypochlorite showed no antifungal efficacy (>300 colonies per plate). Enilconazole (1 : 100), sodium hypochlorite (1 : 32 or 1 : 100), accelerated hydrogen peroxide (1 : 16), and 2% potassium peroxymonosulfate are recommended for decontamination of kennels exposed to dermatophyte pathogens.